THE ROLE OF THE FAMILY IN THE FORMATION OF ECOLOGICAL CULTURE (Conferencea, 2023)
Environmental education in the rapidly developing world of technological progress is an integral part of the educational process. Failure to comply with the requirements of environmental culture can bring modern civilization to the brink of environmental disaster. In the formation of an individual’s ecological culture, education plays a fundamental role. From an early age, it is necessary to teach children to care about the health of our planet, about the protection of the forests, rivers, lakes, seas, birds and animals that surround us, all that vitally important and, undoubtedly, beautiful thing that was created for the harmonious existence of man. As a rule, the first natural teachers of a child, who lay the foundations for his upbringing and the formation of an ecological culture of the individual as his integral part, are members of his family: parents, grandparents, close relatives. The role of the family is comprehensive and comprehensive for children, since the family represents the main unit of society.